Análise hematológica de codornas europeias alimentadas com diferentes níveis de moringa (moringa oleifera) - Mata, Yago Dantas da (Universidade Federal Rural do Semi-Árido, 2018)
Feeding with alternative resources is a tool present in animal production, used to reduce production costs. Moringa oleifera is an attractive alternative because of its protein-rich leaves and is often added to animal feed instead of crude protein. However, moringa presents antinutritional principles, such as saponins, tannins, phytates, among others, that can negatively affect animal health. In this way, the objective was to determine the hematological profile of European quails submitted to different levels of moringa inclusion (0% to 4%) in the diet. Sixty quails from a mixed plot fed with five (5) rations that composed the experimental treatments were used, with 6 replicates per treatment and 20 animals per experimental unit. Blood samples were taken at 28 and 42 days of life of the quail by cardiac puncture with syringes containing one drop of sodium heparin. The blood was then used to obtain erythrocyte parameters, such as red blood cell count, hematocrit, average red blood cell size, hemoglobin amount per red blood cell and mean corpuscular hemoglobin concentration and blood smear for differential leukocyte counts. The means of the parameters were compared between the groups, using regression analysis at the 5% probability level. Leukocyte parameters indicated the occurrence of eosinophilia and lymphopenia at 42 days for quail fed with moringa, however, without affecting the Hetrophil: Lymphocyte ratio, indicating the maintenance of bird welfare. Additionally, young quails at 28 days presented a quadratic effect for monocytes and basophils. There was no significant difference between any of the erythrocyte parameters analyzed according to the inclusion level of the moringa. Quails submitted to the inclusion of moringa in their feeding have a hematological profile similar to that of quails fed commercial feed, certifying the moringa as an alternative in feed and keeping quails in a healthy and satisfactory clinical state.
Monografia
Keywords: Coturnicultura; Leucócitos; Eritrócitos; Alimento alternativo; Bem-estar; Quail production; Leukocytes; Erythrocytes; Alternative food; Welfare; CIENCIAS AGRARIAS::MEDICINA VETERINARIA